Rancang Bangun Aplikasai Pemesanan Katering Berbasis Web - dimas elang setiyoko (Universitas Teknokrat Indonesia, 2022)
The package process and ordering the katering package are carried out by means of the customer directly visiting the katering place. This process has many complaints from consumers who are in the city of Bandar Lampung to come directly to the katering place, when they want to place orders and pay for packages, Packages in companies can be done using internet technology which is better known as (e-promotion). The process of the activities carried out by the (company) in offering food packages through online media (internet), so there is no face-toface between the buyer and the seller of this study resulted in an application that can simplify the booking package foods, based on the results implementai performed by the application ISO / IEC 25010 standard is tested based on functional suitability, performance efficiency and operability, so it can be concluded that it is feasible to be applied to help package ordering and marketing processes..